Mestiçagens e colonização: visões historiográficas sobre a América Portuguesa - Pires Júnior, João Aurélio Travassos (2014)
The concept of miscegenation has changed throughout the years. When it comes to Colonial Brazil, the study of this notion is key for the understanding of its historiography and also for the establishment of the social sciences in the country, being Gilberto Freyre the first and most reliable author to have developed a historiography of miscegenation in Brazil. The present dissertation study aims at analyzing different takes on the the concept of miscegenation, that are found in representative historiographical works that are important for the development of the theme and for the understanding of the concept as well. This study intends to observe the transformations that the concept of miscegenation has suffered, using the reading of five authors that are relevant to the comprehension of the topic: Gilberto Freyre, Carl Degler, Charles Boxer, Serge Gruzinski and Larissa Viana. The referred authors are representative of different historiographical cultures besides they represent different and divergent past points of view about miscegenation. Therefore, there is a trail that begins with the analysis of the concept by Freyre and the balance of antagonism that follows, identifies foreign readings that endorsed it as well as disagreed with it. Next, it is proposed a reading about the inovation of the concept found in the works of french historian Serge Gruzinski and finally it is noted, by reading the works of historian Larissa Viana, an unusual point of view about miscegenation, which is connected to the notion of identity, a current discussion that represents the themes of the most recente cultural studies.